Grit, Work–Life Balance, and Fulfilment of Workplace Needs as Key Aspects of Employee Well-Being: A Study of Employees in Warsaw-Based Corporations - Kolemba, Marcin; Strońska-Szymanek, Anna; Skrok, Joanna (Przegląd Psychologiczny, 2024)
Objective: This study examines the relationships between work–life balance (WLB), grit, and the fulfilment of autonomy, competence, and relatedness needs at work. It also explores selected aspects of employee well-being in Polish corporations in the post-COVID-19 period. The research aims to identify factors associated with employees’ mental well-being in the evolving professional environment. Method: The study involved 77 women and 44 men aged 19–68 who were employed in Warsaw-based branches of corporate firms. The data collection utilized the Work–Life Balance Questionnaire (assessing the balance between professional and private life), the Short Grit Scale (measuring grit), the ‘When I Am at Work’ Questionnaire (evaluating the fulfilment of autonomy, competence, and relatedness needs), and the Psychological Well-Being Scales (measuring psychological well-being). The data analysis included multivariate regression and Spearman’s rho correlation analysis. Results: The multivariate regression analysis revealed that significant predictors of employee well-being include grit (β = .41, p < .001), the fulfilment of relatedness needs (β = .25, p < .001), work-life balance (β = .21, p < .001), and the fulfilment of autonomy needs (β = .16, p < .05). We also identified relationships between the analysed variables and six dimensions of well-being measured using Ryff’s Psychological Well-Being Scales. Conclusion: The study results confirm that work-life balance, grit, and the fulfilment of autonomy, competence, and relatedness needs are significant predictors of the psychological well-being of employees in Polish corporations. In particular, grit and work-life balance may have a substantial impact on employees’ sense of fulfilment and job satisfaction. These findings emphasize the importance of creating a work environment that fosters a balance between professional and personal life while supporting employees’ individual needs.